Pelvic Pain Alters Functional Connectivity Between Anterior Cingulate Cortex and Hippocampus in Both Humans and a Rat Model - Yu, Wenjun; Wu, Xiaoyan; Chen, Yunan; Liang, Zhiying; Jiang, Jinxiang; Misrani, Afzal; Su, Yun; Peng, Yigang; Chen, Jian; Tang, Binliang; Sun, Mengyao; Long, Cheng; et al. (Frontiers in Systems Neuroscience, 2021)
The anterior cingulate cortex (ACC) and hippocampus (HIPP) are two key brain regions associated with pain and pain-related affective processing. However, whether and how pelvic pain alters the neural activity and connectivity of the ACC and HIPP under baseline and during social distress, and the underlying cellular and molecular mechanisms, remain unclear. Using functional magnetic resonance imaging (fMRI) combined with electrophysiology and biochemistry, we show that pelvic pain, particularly, primary dysmenorrhea (PDM), causes an increase in the functional connectivity between ACC and HIPP in resting state fMRI, and a smaller reduction in connectivity during social exclusion in PDM females. Similarly, model rats demonstrate significantly increased ACC-HIPP synchronization in the theta and gamma bands, associating with reduced modulation by ACC-theta of HIPP-gamma and increased levels of receptor proteins and excitation. This study brings together human fMRI and animal research and enables improved therapeutic strategies for ameliorating pain and pain-related affective processing.